PETROLOGY OF ALLENDE DARK INCLUSIONS - Buchanan P.C.; Zolensky M.E.; Reid A.M. (My University, 1997)
Bulk compositions acquired by neutron activation analysis are reported for eight Allende dark inclusions (DIs) and compared with compositions of five DIs previously reported in the literature. Enrichments of the elements Na, K, Br, Ba, Au, and As are generally correlated with increased proportions of porous aggregates predominantly composed of fine-grained, platy to fibrous olivine. These aggregates have been interpreted by some workers as chondrules and inclusions that first were exposed to aqueous alteration, converting anhydrous silicates to phyllosilicates, and later were dehydrated by thermal metamorphism, converting phyllosilicates to olivine. Our data support this interpretation and suggest that the aqueous alteration was open system in character. Feldspathoid grains intergrown with platy to fibrous olivines in porous, olivine-rich aggregates and inclusions of sodalite, nepheline, pentlandite, ilmenite, and spinel in these olivines suggest that phyllosilicates produced during aqueous alteration could accommodate Na, K, Ni, S, etc and are most consistent with a mixture of both saponite and serpentine. Dehydration of saponite would require that the temperature of thermal metamorphism was higher than previously suggested and may have been as high as 800°-900°C. Nonporous rims containing Ca-rich minerals (andradite, hedenbergite) surrounding dark inclusions containing highest proportions of porous, olivine-rich aggregates and slight to moderate depletions of these clasts in Ca relative to bulk Allende suggest that these rims were also the result of redistribution of some elements during dehydration of these clasts caused by thermal metamorphism.